Monster - Myers, Walter Dean 1937- (Scholastic, 1999)
While on trial as an accomplice to a murder, sixteen-year-old Steve Harmon records his experiences in prison and in the courtroom in the form of a film script as he tries to come to terms with the course his life has taken.